Surgical Outcomes of Pulmonary Mucoepidermoid Carcinoma: A Review of 23 Cases - Lee, Geun Dong; Kang, Do Kyun; Kim, Hyeong Ryul; Jang, Se Jin; Kim, Yong-Hee; Kim, Dong Kwan; Park, Seung-Il (The Thoracic and Cardiovascular Surgeon, 2014)
Background The aim of the present study was to evaluate the oncologic characteristics of pulmonary mucoepidermoid carcinoma (PMEC) and the efficacy of surgical resections.Materials and Methods The surgery for PMEC was performed in 23 patients at Asan Medical Center from January 2000 to December 2010. They accounted for 0.8% of all surgically resected pulmonary neoplasm in the center. The medical records of these patients were reviewed retrospectively.Results This study group was composed of 13 males (56.5%) and 10 females (43.5%). Median age was 41 years (range, 10 to 75 years). Complete resection with systematic mediastinal lymph node dissection was performed in all patients. There were three postoperative complications: atelectasis in one patient and chylothorax in two patients. There was no postoperative mortality. The median follow-up duration was 68 months (range, 13 to 115 months). In one patient, recurrent disease was found 73 months after surgery. All patients were followed without mortality until the end of this study. The 5- and 8-year disease-free survival rates were 100 and 90.9%, respectively.Conclusion Complete surgical resection with systematic lymph node dissection is an effective treatment for patients with PMEC and provides favorable prognosis.
Keywords: surgery/incisions; lung cancer treatment; pathology